Detection of novel metabolites of flaxseed lignans in vitro and in vivo - Quartieri, Andrea; García-Villalba, Rocío; Amaretti, Alberto; Raimondi, Stefano; Leonardi, Alan; Rossi, Maddalena; Tomàs-Barberàn, Francisco (Molecular nutrition & food research, 2016)
Scope This study aimed to improve the knowledge of secoisolariciresinol diglucoside (SDG) transformation by human gut microbiota. Methods and results SDG‐supplemented microbiota cultures were inoculated with the feces of five subjects. The same volunteers received a flaxseed supplement for 7 days. SDG metabolites in cultures, feces, and urine were monitored by LC‐ESI‐QTOF and LC‐DAD. In all cultures, SDG was deglycosylated to secoisolariciresinol (SECO) within 12 h. SECO underwent successive dehydroxylations and demethylations yielding enterodiol (4–18% conversion) and enterolactone (0.2–6%) after 24 h. Novel intermediates related to SECO, matairesinol (MATA), and anhydrosecoisolariciresinol (AHS) were identified in fecal cultures. These metabolites were also found after flaxseed consumption in feces and urine (in approximate amounts between 0.01–47.03 μg/g and 0.01–13.49 μg/mL, respectively) in their native form and/or modified by phase II human enzymes (glucuronide, sulfate and sulfoglucuronide conjugates). Conclusions Derivatives of MATA and AHS are described for the first time as intermediates of SDG biotransformation by intestinal bacteria, providing a more comprehensive knowledge of lignan intestinal metabolism. The transformations observed in vitro seem to occur in vivo as well. The detection in urine of SDG intermediates indicates their gut absorption, opening new perspectives on the study of their systemic biological effects. SDG‐supplemented microbiota cultures were inoculated with the feces of five subjects to investigate the metabolism of flaxseed lignans by human gut bacteria. The same volunteers received a flaxseed supplement for 7 days, monitoring lignans in urine and feces. In vitro and in vivo experiments revealed new bacterial intermediates, derivatives of MATA and AHS (in cyan and red, respectively), during transformation into enterolignans. The detection in urine of several intermediates indicates their gut absorption.